Variation on gut microbiota diversity of endangered red pandas (Ailurus fulgens) living in captivity acrosss geographical latitudes - Chen, Wenqi; Chen, Xiaobing; Zhang, Yushuo; Wu, Hong; Zhao, Dapeng (Frontiers in Microbiology, 2024)
The gut microbiome plays important roles in metabolic and immune system related to the health of host. This study applied non-invasive sampling and 16S rDNA high-throughput sequencing to study the gut microbiota structure of red pandas (Ailurus fulgens) for the first time under different geographical latitudes in captivity. The results showed that the two predominant phyla Firmicutes (59.30%) and Proteobacteria (38.58%) constituted 97.88% of the total microbiota in all the fecal samples from north group (red pandas from Tianjin Zoo and Jinan Zoo) and south group (red pandas from Nanjing Hongshan Forest Zoo). The relative abundance of Cyanobacteria in north group was significantly higher than that in south group. At the genus level, Escherichia-Shigella (24.82%) and Clostridium_sensu_stricto_1 (23.00%) were common dominant genera. The relative abundance of norank_f__norank_o__Chloroplast, Terrisporobacter and Anaeroplasma from south group was significantly higher than that of north group. Alpha and Beta analysis consistently showed significant differences between north group and south group, however, the main functions of intestinal microbiota were basically the same, which play an important role in metabolic pathways, biosynthesis of secondary metabolites, microbial metabolism in different environments, and amino acid biosynthesis. The variations in gut microbiota between the northern and southern populations of the same species, both kept in captivity, which are primarily driven by significant differences in climate and diet. These findings provide a deeper understanding of the gut microbiota in red pandas and have important implications for their conservation, particularly in optimizing diet and environmental conditions in captivity.